ANALISA LABA AKUNTANSI DAN LABA TUNAI TERHADAP DIVIDEN KAS PADA PERUSAHAAN FARMASI TAHUN 2013 -2017 - April Lestari; Rakhmawati Oktavianna (Universitas Pamulang, 2019)
This study aims to examine the relationship between accounting earning and cash earning with cash dividend in the pharmaceutical sub-sector companies listed on the Indonesian Stock Exchange during the periode of 2013 to 2017. This study uses secondary data, namely financial report sata from manufacturing companies that are accessed from the official websitre of the Indonesia Stock Exchange. The selection of samples in this study used a purposive sampling technique, namely the technique of collecting samples with certain considerations or sample selection techniques with certain criteria aimed at getting a representative sample according to the specified criteria. The data analysis model used is multiple regression analysis. In addition to using data analysis in this study is an analysismethod with EViews statistical tools version 9. Based on the result of the study show that partially accounting earnings affect cash dividends while cash earnings do not affect cash dividends but simultaneously accounting earnings and cash earnings have a significant effect on cash dividends.